THE FEASIBILITY STUDY OF EVAPORATION COOLING USING POROUS MATERIALS - Yee Yong, Lee; Athilia, Abdullah; Sim Nee, Ting; Yeong Huei, Lee (Penerbit UMT, 2022)
Human thermal comfort evaluation is essential to avoid heat illness and can be used as an indicator for city development and thermal manikin is one of the tools for it. In this paper, porous materials such as red clay, white clay and plaster are investigated for outdoor thermal comfort evaluation in developing sweating thermal manikin. Unglazed red clay and white clay pots are filled with water and covered with an aluminium foil. However, unglazed plaster pots are filled with absorbent cotton wool saturated with water. They are compared with control specimens (those without water filling). The weights of the pots are measured every hour to check the evaporation rate and the surface temperatures and ambient temperature of all pots are also measured. Based on the analysis, the rate of evaporation for the porous material increases as the ambient temperature increase. The surface temperature of control samples was slightly higher than the samples filled with water where the increase in ambient temperature raised the evaporation cooling effect. In comparison, the white clay pot with its porosity characteristics shows more consistent results. The outcome of this investigation can be used as a reference for the development of sweating thermal manikin to achieve sustainable cities status